2020
DOI: 10.1007/s10955-020-02573-5
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Hyperspheres via Extreme Value Theory: Implications for Measuring Attractor Dimensions

Abstract: The attractor dimension is an important quantity in information theory, as it is related to the number of effective degrees of freedom of the underlying dynamical system. By using the link between extreme value theory and Poincaré recurrences, it is possible to compute this quantity from time series of high-dimensional systems without embedding the data. In general d < n, where n is the dimension of the full phase-space, as the dynamics freezes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The dynamical systems approach has been successfully applied to a variety of climate fields and datasets (Faranda et al 2017a(Faranda et al , b, 2019a(Faranda et al ,2020Messori et al 2017;Buschow and Friedrichs 2018;Rodrigues et al 2018;Brunetti et al 2019;Hochman et al 2019Hochman et al , 2020De Luca et al 2020a, b;Pons et al 2020). Specifically, it has been shown that d and θ −1 can provide an objective dynamical characterization of synoptic systems over both the North Atlantic (Faranda et al 2017a;Messori et al 2017;Rodrigues et al 2018) and the Eastern Mediterranean (Hochman et al 2019(Hochman et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical systems approach has been successfully applied to a variety of climate fields and datasets (Faranda et al 2017a(Faranda et al , b, 2019a(Faranda et al ,2020Messori et al 2017;Buschow and Friedrichs 2018;Rodrigues et al 2018;Brunetti et al 2019;Hochman et al 2019Hochman et al , 2020De Luca et al 2020a, b;Pons et al 2020). Specifically, it has been shown that d and θ −1 can provide an objective dynamical characterization of synoptic systems over both the North Atlantic (Faranda et al 2017a;Messori et al 2017;Rodrigues et al 2018) and the Eastern Mediterranean (Hochman et al 2019(Hochman et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…There, the authors show that finite-time deviations of d and θ from the asymptotic, unknown values contain information about the underlying system, since they are linked to the presence of unstable or periodic points of the dynamics. Similarly, both analytical and empirical evidence from Pons et al (2020) shows that, although affected by the curse of dimensionality, estimates of d from finite time series may be used in a relative sense to characterise the dynamics of a system -i.e. by comparing values of d to one another.…”
Section: Theoretical Underpinnings Of the Dynamical Systems Frameworkmentioning
confidence: 99%
“…Caby et al [14] study both the case of deterministic and of stochastic dynamical systems, and present also an example of analysis of actual atmospheric data. Extreme value theory is used by Pons et al [100] to propose a way to address well-known problem of the curse of dimensionality in estimating the Hausdorff dimension of the attractor from time series. The methodology is applied to study recurrences in synthetically generated as well as real-life financial and climate data and define the degree of non-randomness of the system.…”
Section: This Special Issuementioning
confidence: 99%